Impact of Sugammadex on Clinical and Patient-Centered Outcomes: Beyond Neuromuscular Recovery - Ji-Yoon Jung; Tae-Yun Sung (Journal of Clinical Medicine, 2026)
Background: Residual neuromuscular blockade remains an important contributor to postoperative morbidity. Sugammadex provides rapid and predictable reversal of rocuronium- and vecuronium-induced blockade and reduces residual neuromuscular blockade more effectively than conventional anticholinesterase-based reversal. Methods: This structured narrative review was informed by searches of PubMed/MEDLINE and the Cochrane Library from database inception to 20 August 2026. Reference lists of relevant guidelines, systematic reviews, and eligible studies were also screened. Randomized trials, observational studies, systematic reviews, and meta-analyses reporting clinical or patient-centered outcomes after sugammadex or neostigmine-based reversal were prioritized. Results: The most consistent evidence relates to neuromuscular recovery and residual blockade. Observational studies and meta-analyses suggest possible reductions in selected postoperative pulmonary complications with sugammadex, but findings are heterogeneous and do not establish a uniform causal benefit. Potential differences have also been reported in hemodynamic events, urinary retention, early postoperative nausea and vomiting, and early physiological recovery. Evidence regarding postoperative pain, delirium, overall morbidity, mortality, length of stay, healthcare costs, and patient-reported recovery remains mixed and context-dependent. Important safety considerations include bradycardia, hypersensitivity and anaphylaxis, transient changes in coagulation assays, recurrent block after inadequate dosing, and prolonged exposure in severe renal impairment. Conclusions: Sugammadex may be associated with favorable selected postoperative outcomes, but it should not be regarded as an independent determinant of recovery. Its clinical effects must be interpreted as part of optimized neuromuscular management incorporating quantitative monitoring, blockade-depth-appropriate dosing, confirmation of recovery, and comprehensive perioperative care.